ANALISIS PENDIDIKAN KARAKTER DALAM MEWUJUDKAN KESADARAN TERHADAP LINGKUNGAN BAGI SISWA SMKN – 4 PEKANBARU - Sujarna Sujarna; Mirna Ilza; Zulfan Saam (Jurnal Ilmu Lingkungan, 2014)
The Analysis of character education in creating awareness about the environment hasbeen conducted at SMK - 4 Pekanbaru in June 2013. This study uses a survey throughinterviews to the questioner and respondent. The research concludes that (1) the schoolcharacter education in the category of good it has done with students indicatorsappropriate waste disposal between organic and inorganic species, (2) environmentalawareness in the category of students is also a good indicator of the level of activity inparticular on the use of waste 4 vocational school in Pekanbaru environment. So withthe character education can be instrumental in improving students' environmentalawareness SMKN 4 Pekanbaru Riau Province labih both within academia and outsideof that environment.